Research on the effect of water-cooling steel pipe on preventing spontaneous combustion of coal pile and its thermal migration behavior - Chunming Ai; Shuang Xue; Li Zhang; Qinyuan Zhou (Scientific Reports, 2024)
Abstract During the storage and transportation process after mining, coal piles are placed in open environments, making them prone to self-heating and spontaneous combustion due to the nature of coal and factors like natural wind flow. In recent years, there have been frequent spontaneous combustion incidents involving coal piles, posing significant safety risks. To effectively prevent and control spontaneous combustion disasters in open-air coal storage piles, we propose a method involving the arrangement of water-cooling steel pipes within the coal piles. This method applies theories of coal spontaneous combustion mechanisms, porous media heat transfer, and non-isothermal pipeline heat transfer. The multi-physics coupling model of COMSOL numerical simulation software is used to analyze the spontaneous ignition process and prevention effect of open pit coal pile. In the model, the thin material transfer of porous media is taken as the oxygen concentration field, the heat transfer of porous media is taken as the temperature field, and the free and porous media flow is taken as the air seepage velocity field. The simulation results of the spontaneous combustion process in the coal pile indicate that the high-temperature zone of spontaneous combustion is situated within the range of 0.5 ~ 1.5 m inside the wind-facing surface and extends 0.5 m above the ground level. These findings serve as a basis for determining the optimal placement of water-cooling steel pipes within the coal pile. The simulation results of a single water-cooling steel pipe demonstrate a positive correlation between the cooling effect on the coal pile and the water cool flow, and a negative correlation with the water cool temperature. Additionally, the cooling radius of the water-cooling steel pipe is determined by the circumference of the pipe and remains unaffected by the water cool flow. Finally, simulations were conducted to evaluate the cooling effect of multiple rows of steel pipes, and optimal arrangement parameters were determined: a center distance between steel pipes of 1 m and a water cool flow rate of 1500 L/min. As a result, the onset of the self-heating period in the coal pile was delayed by 11 days, and the spontaneous combustion period was extended by 56 days. The arrangement of water-cooling steel pipes in the coal pile has demonstrated significant efficacy in preventing and controlling spontaneous combustion.